Overview of Knowledge and Attitudes Towards Symptoms of Sexually Transmitted Infections (STIs) at SMAN 8 Jambi City - Amallia, Bela; Mulyani, Sri; Mekeama, Luri (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Background: Sexually transmitted infections (STIs) are a common reproductive health problem among adolescents due to risky behavior and a lack of knowledge and attitudes regarding prevention. Adolescents' knowledge and attitudes play a very important role in efforts to reduce the risk of STI transmission. Objective: This study aims to determine the characteristics of students, their level of knowledge, attitudes, and the incidence of STIs among students at SMAN 8 Kota Jambi. In addition, this study also aims to determine the relationship between knowledge and attitudes towards the signs and symptoms of STIs among students at SMAN 8 Kota Jambi. Methods: This study was an analytical study using a cross-sectional approach. The study population consisted of all 11th grade students at SMAN 8 Jambi City, with a sample size of 90 respondents selected using proportional stratified random sampling. The research instrument was a questionnaire that had been tested for validity and reliability. Results: The results showed that most respondents had good knowledge (86.7%) and positive attitudes (96.7%). STI symptoms were mostly in the low-risk category. Conclusion: The better the students' knowledge and attitudes, the lower the risk of STI symptoms. It is hoped that schools and health workers will continue to improve education about STIs to prevent transmission from an early age. Keywords: Knowledge, Attitude, Sexually Transmitted Infections, Adolescents.